Numerical simulation of the flow around the ahmed vehicle model - Franck, Gerardo (2009)
The unsteady flow around the Ahmed vehicle model is numerically solved for a Reynolds number of 4.25 million based on the model length. A viscous and incompressible fluid flow of Newtonian type governed by the Navier-Stokes equations is assumed. A Large Eddy Simulation (LES) technique is applied together with the Smagorinsky model as Subgrid Scale Modeling (SGM) and a slightly modified van Driest near-wall damping. A monolithic computational code based on the finite element method is used, with linear basis functions for both pressure and velocity fields, stabilized by means of the Streamline Upwind Petrov-Galerkin (SUPG) scheme combined with the Pressure Stabilizing Petrov- Galerkin (PSPG) one. Parallel computing on a Beowulf cluster with a domain decomposition technique for solving the algebraic system is used. The flow analysis is focused on the near-wake region, where the coherent macro structures are estimated through the second invariant of the velocity gradient (or Q-criterion) applied on the time-average flow. It is verified that the topological features of the timeaverage flow are independent of the averaging time T and grid-size.